Metal (Ni, Pd, and Pt)-Doped BS Monolayers as a Gas Sensor upon Vented Gases in Lithium-Ion Batteries: A First-Principles Study - Li, Ming; Wang, Xue-Feng (Langmuir, 2024)
Real-time monitoring of the vented gases emitted by the thermal runaway of lithium-ion batteries (LIBs) is of great significance to the normal use of LIBs. We study systematically the adsorption and sensing performances of pristine and metal-doped BS monolayers to five typical gases (CO, CO , CH , C H , and C H ) emitted from LIBs employing the first-principles method. The adsorption structure and energetics, charge transfer, band structure, density of states, sensitivity, and recovery time are simulated and analyzed. Outstanding sensing properties are predicted for the Ni-, Pd-, and Pt-doped BS monolayers, although their recently synthesized pristine counterpart shows little sensing potential for those gases. The magnitude of the adsorption energy increases from 0.249 eV to 2.32 eV (Ni-BS), 1.954 eV(Pd-BS), and 2.994 eV (Pt-BS) for the CO gas after doping. Besides, significant variation of band gap is observed after gas adsorption in doped BS nanosheets, which leads to huge theoretical values of the sensitivity. The sensitivity for CO, CO , CH , C H , and C H on Pt-BS may reach up to 5.87 × 10 , 1.57 × 10 , 1.81 × 10 , 8.33 × 10 , and 8.18 × 10 , respectively. In addition, the calculated recovery times indicate that the doped BS monolayers have strong selectivity for the adsorption and detection of these five gases. The three metal-doped BS monolayers should have great potential for application in sensors monitoring the gases emitted from LIBs.